Factors Affecting Firm Performance In Manufacturing Companies In Indonesia Stock Exchange - Agustin Ekadjaja; Andi Wijaya; Vernetta (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2021)
The aim in this reseach is to find empirical evidence to finding the influence between leverage, liquidity, growth, and firm size towards firm performance. The reseach method used was purposive sampling with a total sample of 44 firms listed on the Indonesian Stock Exchange (IDX). The subject of this reseach is all manufacture companies that are listed in Bursa Efek Indonesia for the period of 2017 until 2019. The type of data used is secondary data. Application that is used in this reseach is Eviews 11. This reseach shown that there are no significant influence between liquidity and firm age towards firm performance, there are positive significant influence between growth and firm size towards firm performance, and there is negative significant influence between leverage towards firm performance. The implication of this research is the need for high quality management that will encourage the firm to improve its performance in order to be able to determine the right strategies to be able to compete and then to maintain its sustainability.